Prognosis prediction performs better in patients with non-cirrhosis hepatitis B virus-related acute-on-chronic liver failure than those with cirrhosis - Yu, Xia; Li, Hai; Tan, Wenting; Wang, Xianbo; Zheng, Xin; Huang, Yan; Li, Beiling; Meng, Zhongji; Gao, Yanhang; Qian, Zhiping; Liu, Feng; Lu, Xiaobo; et al. (Frontiers in Microbiology, 2022)
Background: The accurate prediction of outcome of hepatitis B virus related acute-on-chronic liver failure (HBV-ACLF) is impeded by the population heterogeneity. The aim of the study was to assess the impact of underlying cirrhosis on the performance of clinical prediction models (CPMs). Methods: Using data from two multi-center, prospective cohorts of patients with HBV-ACLF, the discrimination, calibration and clinical benefit were assessed for CPMs predicting 28-day and 90-day outcome in patients with cirrhosis and those without, respectively. Results: A total of 919 patients with HBV-ACLF were identified by COSSH criteria, including 675 with cirrhosis and 244 without. COSSH-ACLF IIs, COSSH-ACLFs, CLIF-C ACLFs, TPPMs, MELDs and MELD-Nas each was a strong predictor of short-term mortality in patients with HBV-ACLF. In contrast to a high model discriminative capacity in ACLF without cirrhosis, each prognostic model represents a marked decline of C-Index, Net Reclassification Index (NRI) and Integrated Discrimination Improvement (IDI) in predicting either 28-day or 90-day prognosis of patients with cirrhosis. The hazard analysis identified largely overlapping risk factors of poor outcomes in both subgroups, while serum bilirubin were specifically associated with short-term mortality in patients with cirrhosis and blood urea nitrogen in patients without cirrhosis. Subgroup analysis in patients with cirrhosis showed a decline of discrimination of CPMS in those with ascites or infections compared to that in those without. Conclusions: Predicting short-term outcome of HBV-ACLF by CPMs is optimal in patients without cirrhosis but limited in those with cirrhosis, at least partially due to the complicated ascites or infections.